EKSISTENSI KERAJINAN PERAK KOTO GADANG SUMATERA BARAT - Hendra Hendra (Institut Seni Indonesia Yogyakarta, 2018)
Koto Gadang Silverwork is located in District IV Koto Agam Regency which is one of the craft centers that exist near Bukittinggi. The existence of silver handicraft products that produced in Koto Gadang has started since the Dutch colonial era until now. Silver handicrafts grow and develop according as the time continue . This can be seen from changes in the function and shape of existing silver handicrafts that equal with the changes of the community. Silver handicraft products Koto Gadang can be classified into jewelry products such as necklaces and bracelets, as well as souvenir products such as miniature of clock tower. The products that produced by craftsmen are represent of their existence and their efforts to adjust the products to public demand. To maintain the quality of silver products, craftsman only sell the products in a limited market. This way is taken to maintain public confidence in the silver craft itself. With cultural changes, the silver handicrafts Koto Gadang face the challenges and obstacles that make artman must be clever in maintaining consumer confidence. This is closely related to the survival of silverwork itself around the supporting community. Keyword : existence, silver, Koto Gadang Kerajinan perak Koto Gadang terletak di Kecamatan IV Koto Kabupaten Agam yang merupakan salah satu sentra kerajinan yang ada di dekat Kota Bukittinggi. Eksistensi produk kerajinan perak yang dihasilkan Koto Gadang sudah dimulai semenjak zaman penjajahan Belanda hingga sekarang. Kerajinan perak tumbuh dan berkembang sesuai dengan perkembangan zaman. Hal ini dapat dilihat dari perubahan fungsi dan bentuk kerajinan perak yang ada yang menyesuaikan dengan perubahan masyarakatnya. Produk kerajinan perak Koto Gadang bisa dikelompokkan menjadi produk perhiasan, seperti kalung dan gelang, serta produk cenderamata, seperti miniatur Jam Gadang. Produk yang dihasilkan oleh perajin merupakan bentuk eksistensi mereka dan usaha mereka untuk menyesuaikan produk yang dihasilkan dengan permintaan masyarakat. Untuk menjaga kualitas produk kerajinan perak tersebut, perajin hanya menjual produk yang dihasilkan dalam pasar yang terbatas. Hal ini dilakukan untuk menjaga kepercayaan masyarakat terhadap kerajinan perak itu sendiri. Seiring perubahan budaya mengakibatkan kerajinan perak Koto Gadang menghadapi tantangan dan hambatan yang membuat perajin harus pandai-pandai dalam menjaga kepercayaan konsumen. Hal ini berhubungan erat dengan keberlangsungan kerajinan perak itu sendiri di masyarakat pendukungnya.Kata Kunci : eksistensi, perak, Koto Gadang